Taking a closer look at the speaking of ideal self of Spanish undergraduates - Aránzazu García-Pinar (Universitas Syiah Kuala, 2021)
Over the past fifteen years, research on second language (or L2) motivation has been dominated by Dörnyei's influential paradigm, the L2 Motivational Self System. Students' imagined visualisations are key components in this theory, as those students who have a clear ideal self-image with an L2 component will probably be more motivated to learn a language than others that have not established a desired future state goal for themselves. This article reports the qualitative findings of a mixed-method study that explored the effects of a multimodal intervention with influential speakers on changing the students' attitudes in public speaking. Semi-structured interviews and open-ended questionnaires were conducted with 11 engineering undergraduates, who volunteered to take part in the present study. Qualitative data showed that the multimodal intervention accompanied by goal setting (i.e., students' classroom oral presentations) triggered an increase in some students' future speaking selves. Six of the eleven students demonstrated a slight development in their levels of linguistic self-confidence, which made their vision of their ideal L2 speaking selves more realistic and clearer. The article discusses the implications of these findings and calls for a pedagogical shift that embraces more opportunities to assess the multimodal skills and strategies students need to become fluent L2 speakers.